Etnoconhecimento de plantas medicinais cultivadas em quintais na comunidade Mamangal Grande, rio Meruú, Igarapé-Miri, Pará - SANTOS, Elda Quaresma dos (2019)
The city of Igarapé-Miri is located in the North region, State of Pará. The Mamangal community is located on the banks of the Mamangal Grande River, between the Meruú-Açu and Maiauatá rivers. This study aimed to research the traditional knowledge about the manipulation, uses and therapeutic indications of the plants used by the residents of the Mamangal community. The selection of the collaborators was done through the "snowball" methodology. Twenty participants were included, in the age group of 30 to 76 years, all were literate and the plant with predominance of use was the mastruz, to treat intestinal affections. The medicinal flora of the backyards of the Mamangal community presented a high diversity of species used in local medicine.